MONITORING OF LUBRICANT OIL OF HYDRAULIC SYSTEMS AS PART OF PREDICTIVE MAINTENANCE - Magalhães Viegas Junior, Daniel (Journal of Interdisciplinary Debates, 2024)
Hydraulic systems are widely used in different industries, such as civil construction, aerospace, automotive, oil, among others. The hydraulic fluid or lubricating oil of these systems is an important source of information regarding the state of the machines. In this way, the analysis of lubricating oil proves to be an important and effective tool to monitor the condition of components of hydraulic systems. Since the emergence of predictive maintenance, researchers have been dedicated to developing methods of online monitoring of hydraulic fluids in order to prevent failures, increase safety and reduce maintenance costs. Therefore, the present work sought to carry out a discussion on the importance of monitoring the hydraulic fluid, bringing the main methods of analysis and the most recent advances.